2011
DOI: 10.1002/art.33312
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler ultrasound, but not low‐field magnetic resonance imaging, predicts relapse and radiographic disease progression in rheumatoid arthritis patients with low levels of disease activity

Abstract: Objective. Subclinical inflammation and radiographic progression have been described in rheumatoid arthritis (RA) patients whose disease is in remission or is showing a low level of activity. The aim of this study was to compare the ability of ultrasonography and magnetic resonance imaging (MRI) to predict relapse and radiographic progression in these patients.Methods. Patients with RA of short or intermediate duration that was either in remission or exhibiting low levels of activity according to the Disease A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 41 publications
6
105
0
16
Order By: Relevance
“…Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]). …”
Section: M6 P Referencessupporting
confidence: 59%
“…Inoue et al found DAS28-CRP 2.3 matched DAS28-ESR remission in Japanese patients [10].The present study suggests that composite scores overestimate remission and patients retain subclinical inflammation found on MRI. Our results join the various studies that have proven the dissociation between clinical remission according different composite scores and remission in imaging either by ultrasound (Ramirez J et al [11]) or MRI (Gandjbakhch F et al [12]) or both (Foltz V et al [13]). …”
Section: M6 P Referencessupporting
confidence: 59%
“…Therefore, a direct causal relation between clinically inflamed synovitis and structural damage progression seems unclear (11). However, the predictive value of subclinical synovitis, assessed by US or MRI, on structural damage has been suggested in RA patients treated with tumor necrosis factor blockers (21) and for patients in clinical remission (22).…”
Section: Discussionmentioning
confidence: 99%
“…US is widely used in the early diagnosis of RA, particularly in the introduction and application of high frequency color Doppler US, which can monitor joint effusion, blood flow change in the synovium and synovial thickening (25). Furthermore, US may be used to monitor disease status and predict disease recurrence, providing an effective and valuable evaluation of treatments (26). Furthermore, US is more acceptable for patients, as it is relatively simple, cheap and does not use radiation (4).…”
Section: Discussionmentioning
confidence: 99%